Cash Waqf for education: Prospects and challenges / Ridzwan Bakar. - Bakar, Ridzwan (Universiti Teknologi MARA Selangor, 2018)
This article is written based on author’s personal experience with waqf program implementation (philantrophy activities) mainly in executing cash waqf for education in Malaysia, Indonesia and Cambodia. In particular, the article provides brief literature on waqf and cash waqf, describes success story, highlights prospects and challenges in implementing cash waqf for education.